WAKTU TANAM KAPAS DI SULAWESI SELATAN - PRIMA D. RIAJAYA; M. SHOLEH; F. T. KADARWATI; M. RIZAL (Jurnal Penelitian Tanaman Industri, 2001)
Cotton Planting Times in South SulawesiClimatic elements particularly the rainfall strongly influences successful production of rainfed cotton (Gossypium hirsutum). Planting times determined based on more than 20 years daily rainfall data. The rainfall was analyzed using Markov Chain First Order Probability and dryspell probability methods The rainfall data were collected from 46 rainfall stations over Jeneponto, Soppeng, Wajo, Gowa, Bone. Bulukumba. Bantaeng, and Takalar. The planting times varied from the irst week to the fourth week of December for Jeneponto, Takalar, and mostly Gowa. The planting times in Soppeng and Wajo were ranged from the third week of February to the third week of March. Morever, cotton planting times in Bone and Bulukumba were ranged from the third week of March to the third week of April.